Conclusion: State power (and its limits) in internet governance - Tusikov, Natasha; Haggart, Blayne; Scholte, Jan Aart (Power and Authority in Internet Governance, 2021)
In the conclusion, we synthesise insights from the previous chapters as they relate to the role of the state in internet governance today and into the future, focusing on five main points. First, current trends show widespread state attempts to exert greater control in internet governance, and these government initiatives often conflict with the private regimes that have previously dominated in areas such as internet infrastructure. Second, business plays significant constraining and enabling roles in shaping state power vis-à-vis the internet. Third, both authoritarian and democratic states (in different ways and to different degrees) face technical, social and economic limitations when they seek to exert "sovereignty" in internet governance. Fourth, multistakeholder internet governance in practice often puts both state and civil society actors in a secondary role behind business and technical interests. Fifth, the US government continues to have a consequential role in the overall regime complex for internet governance. Finally, we offer some thoughts on future lines of research concerning the role of the state in internet governance.